The word” light and darkness” in the Holy Quran and their rhetorical secrets: لفظة النور والظلمات في القرآن الكريم، وإيحاءاتهما البلاغية - Kaffah, Silmi; Nazish, Dr. Samia (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
The Noble Qur’an will remain lofty, its miraculousness is great, and will remain until the Day of Judgment. One of the most important reasons for the inimitability of the Qur’an is the order in speech, which does not mean that its words continued in pronunciation, but that their connotations were consistent and their meanings converged in the manner required by the mind. On the basis of this precise and profound aspect, which was manifested in the Qur’anic style, the selection of this study came under the title: “The Word of Light and Darkness in the Holy Qur’an, and Their Rhetorical Revelations.” This study aims to reflect on the verses of light and darkness, understand their meanings, and to reveal the aesthetics of rhetorical overtones according to the words. In this study the subject is dealt with using the descriptive method and the analytical method in order to reach the suggestive connotations affecting the verses of light in the minds of the recipient.